2022
DOI: 10.3390/molecules27020462
|View full text |Cite
|
Sign up to set email alerts
|

Study of Semi-Dry High Target Solidification/Stabilization of Harmful Impurities in Phosphogypsum by Modification

Abstract: Phosphogypsum (PG) treatment is one of the research hotspots in the field of environmental protection. Many researchers both at home and abroad have devoted themselves to studies on harmless resource treatment of PG, but the treatment technology is unable to meet the demand of PG consumption due to the huge production and storage demands. In order to solve the problem of PG pollution, this study explored the different solidified effects of various modification formulations on the hazardous components in PG, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Wu et al. found that the 0.5% calcium carbide slag, as an alkaline conditioning agent, mixed with 0.4% silicate cement, 0.3% polymeric aluminium chloride and CaCl 2 had a significant curing effect on P and F. The leaching toxicity met the requirements of the relevant standard ( Wu et al., 2022c ), laying a good foundation for PG-based eco-remediation materials and fillers. The use of calcium carbide slag as an alkali neutraliser for PG has the advantages of low economic cost, simple process, and high feasibility.…”
Section: Pretreatment Methods Of Pgmentioning
confidence: 99%
“…Wu et al. found that the 0.5% calcium carbide slag, as an alkaline conditioning agent, mixed with 0.4% silicate cement, 0.3% polymeric aluminium chloride and CaCl 2 had a significant curing effect on P and F. The leaching toxicity met the requirements of the relevant standard ( Wu et al., 2022c ), laying a good foundation for PG-based eco-remediation materials and fillers. The use of calcium carbide slag as an alkali neutraliser for PG has the advantages of low economic cost, simple process, and high feasibility.…”
Section: Pretreatment Methods Of Pgmentioning
confidence: 99%
“…Wu et al [30] studied the effect of the hardening of various modification compositions on hazardous components of phosphogypsum (Yunnan Yuntianhua Environmental Protection Technology Co., Ltd., Wuhan, China) using calcium carbide slag from industrial solid waste (CCS) as an alkaline regulator, Portland cement (PC), polyaluminum chloride (PAC), and calcium chloride as the main raw materials of the solidification, and the water content stabilization formula in phosphogypsum as the reaction medium. The results showed that CCS (0.5%), PC (0.4%), and PAC (0.3%) have a more significant hardening effect on phosphorus (P) and fluoride (F − ), which makes it possible to obtain materials and fillers based on phosphogypsum with low economic costs.…”
Section: Introductionmentioning
confidence: 99%